Facile and green synthesis of multifunctional nitrogen-doped carbon quantum dots from Ginkgo biloba leaves for antibacterial, antioxidant, and bioactive coating applications - Singh, Ajit Kumar; Itkor, Pontree; Zainal Abedin, Nur Hanani; Lee, Myungho; Gaikwad, Kirtiraj K.; Lee, Youn Suk (Elsevier, 2025)
As the demand for sustainable and functional food packaging increases, carbon quantum dots (CQDs) have demonstrated immense potential for incorporation into biopolymer-based active packaging and coatings. We report a green and sustainable hydrothermal approach for the synthesis of surface-passivated nitrogen-doped carbon quantum dots (N-CQDs) using Ginkgo biloba leaves as a renewable carbon precursor. Polyethylene glycol (PEG) acted as a passivating agent, yielding N-CQDs with strong cyan fluorescence, excitation-dependent emission, and high aqueous solubility. The synthesized N-CQDs exhibited remarkable monodispersity (2.4 ±0.72 nm), a surface charge of − 15.1 mV, and a fluorescence quantum yield of 9.69 %. The radical scavenging efficiency of N-CQDs was notably improved, achieving 72.26 % for DPPH and 96.97 % for ABTS, indicating their strong antioxidant functionality. Inhibition zones of 16 mm against E. coli and 18 mm against S. aureus confirmed their antimicrobial efficacy. Cytotoxicity tests confirmed that the prepared N-CQDs were non- toxic to L929 cells even at a higher concentration of 500 μg/mL. N-CQDs incorporated within CMC-based coatings displayed significant antioxidant and antimicrobial properties, successfully inhibiting fungal growth and prolonging mandarin storage life over 15 days. These findings highlight the potential of N-CQDs as sustainable, biocompatible, and versatile nanomaterials, offering improved functionality in active food packaging applications.